Analysis of casson nanofluid transport rates near a vertical stretching sheet with dissipation and slip effects - Walelign, Tadesse (Frontiers in Applied Mathematics and Statistics, 2025)
Practical applicationsAnalysis of Casson nanofluid transport rates near a vertical stretching sheet with dissipation and slip effects will provide relevant information for practitioners to make informed decisions in handling real flow systems. Hence, the present study will contribute in not only supplementing the theoretical gaps for the scientific community but also improving the working efficiency of practical flow systems in manufacturing industries and the quality of their products.PurposeThis study mainly focused on examining the rates of hydromagnetic transport phenomena of Casson nanofluid near a vertical surface in the presence of slip, dissipation, and cross-diffusion effects. Based on the underlying conservation laws in physical sciences and significant model assumptions, a more comprehensive mathematical model is taken into account. Efforts are made to analyze variations in the rates of heat, mass, and momentum transfer against the continuous change of the variables.MethodologyThe solutions for the resulting model equations are explored with the help of the optimal homotopy analysis method.FindingsAmong the results of the study, it is determined that the rate of heat transfer between the solid surface and the surrounding fluid is enhanced by increasing the effect of magnetic field (B > 3.5), thermal radiation (Rd > 2.5), or concentration buoyancy force (Gc > 5). On the other hand, the mass transfer near the solid surface can be assisted by increasing the effect of thermal diffusion (Sr > 0), heat generation (Q > 2), thermal radiation (Rd > 2.5), and concentration buoyancy force (Gc > 3). Furthermore, the rate of momentum transfer of the fluid flow near the solid surface can be facilitated by increasing the effect of flow unsteadiness (A > 2.5) or heat sink (Q < −4).OriginalityMost of the available studies on the physical quantities of practical interest were made based on presenting their variations at only some selected values of the parameters. Such analysis cannot give full information about the complete behavior of the quantities in response to the governing parameters. Thus, in this study a considerable attention is given to how the fluid transport rates vary with the relevant factors in a continuous domain of the parameters. Furthermore, the study considers a more comprehensive mathematical model in the area under consideration and the resulting equations are solved by an efficient optimal homotopy analysis method.